Leanness achievement through people development system in implementing lean process management - A. Perumal, Puvanasvaran; Tay, C. H.; Megat Ahmad, Megat Mohamad Hamdan; Tang, Sai Hong; Mohd Yusuff, Rosnah; Muhamad, Mohd Razali; Hamouda, Abdel Magid Salem (Science Publications, 2009)
Problem Statement: Many organizations fail to unlock the infinite potential of their workforce. In that case there will be more overhead, with more layers of management, which in turn could cause slower reaction times in fast changing business. Employees should only start, run and optimize the process, even developing themselves with the aid of People Development Systems (PDS), when they are under-equipped to handle the process. Approach: This study evaluate the improvement for the degree of leanness and top management commitment possessed by the company after PDS was implemented in the Kitting Department of the aerospace company. Quantitative measures were used to document the case study. Results: Leanness and top management commitments for kitting department shows significant improvement and strong relationship with problem solving capability which lead to achievement of better Leanness level through the infrastructural investments. Conclusion: Hence, the findings suggest or even prove that successful implementation of PDS which developed and equipped employees can provide a wide array of benefits to any company, irrespective of the industry in which it operates.